The unscented filter as an alternative to the EKF for nonlinear state estimation: a simulation case study - Romanenko, Andrei (2004)
The Kalman filter has been widely used for estimation and tracking of linear systems since its formulation in 1960 due to its simplicity and robustness. In many chemical engineering applications the extended Kalman filter (EKF) is often used to deal with certain classes of nonlinear systems. In spite of that, designing an EKF for highly nonlinear processes is not a trivial task, particularly those involving highly exothermic reactions. In this work we compared the performance of a new technique, the unscented filter, with that of the extended Kalman filter. The unscented filter produced better results without performing potentially ill-conditioned numerical calculations and linearly approximating the evolution of the state vector covariance.